Mass measurements of isolated objects from space-based microlensing - Zhu, Wei; Hundertmark, Markus; Tsapras, Yiannis; Schmidt, Robert W.; Wambsganß, Joachim (The astrophysical journal, 2016)
We report on the mass and distance measurements of two single-lens events from the 2015 Spitzer microlensing campaign. With both finite-source effect and microlens parallax measurements, we find that the lens of OGLE-2015-BLG-1268 is very likely a brown dwarf (BD). Assuming that the source star lies behind the same amount of dust as the Bulge red clump, we find the lens is a 45 ± 7 ##IMG## [http://ej.iop.org/images/0004-637X/825/1/60/apjaa2256ieqn1.gif] $M_\rmJ$ BD at 5.9 ± 1.0 kpc. The lens of of the second event, OGLE-2015-BLG-0763, is a 0.50 ± 0.04 ##IMG## [http://ej.iop.org/images/0004-637X/825/1/60/apjaa2256ieqn2.gif] $M_ødot $ star at 6.9 ± 1.0 kpc. We show that the probability to definitively measure the mass of isolated microlenses is dramatically increased once simultaneous ground- and space-based observations are conducted.